Virtual Reality and Artificial Intelligence for Acrophobia Mitigation: An Analysis of EEG and Heart Rate Physiological Data - Chiew Mei, Chan (Science Publications, 2025)
The advent and subsequent proliferation of virtual reality (VR) technology have seen its application extended beyond entertainment to the medical field. One such application is in the treatment of acrophobia, a common and costly phobia that often sees patients discouraged by long waiting lists and complex treatment processes. This research evaluated the efficacy of VR and artificial intelligence (AI) in treating acrophobia, focusing specifically on the relative merits of two biophysical measurements: heart rate (HR) and electroencephalogram (EEG). Utilizing graded exposure therapy, acrophobic individuals were gradually exposed to a VR environment commensurate with their acrophobia severity level. In lieu of a traditional therapist, the severity level and corresponding exposure were determined by an AI agent using a Behavioural Avoidance Test (BAT). This AI agent was also programmed to provide tasks and encouragement to the user in the VR environment. This approach not only negates the safety risks typically associated with exposure therapy but also provides an immersive and realistic environment through high-resolution graphics across seven different height environments. Inclusion and exclusion criteria, as well as the severity of acrophobia, were determined using the Visual Height Intolerance Severity Scale (vHISS). Post-therapy fear levels were measured using the Attitudes Towards Heights Questionnaires (ATHQ). Findings were analysed using the Mann-Whitney U test to check for significant differences between the two biophysical measurements. Results showed no significant difference between heart rate (HR) and electroencephalogram (EEG) measurements in gauging fear response during VR therapy. The utilization of VR and AI in treating acrophobia remains promising. The ATHQ score decrease highlights VR and AI's potential for effective acrophobia therapy, offering immersive experiences to improve outcomes. Future research should aim to replicate these findings in a sample size that exceeds the current one and encompasses greater demographic diversity, thus enhancing the generalizability of these results.